Search 75,760 tutors
FIND TUTORS
Ask a question
0 0

(sin^6 x)/(1- tan^2 x) + (cos^6 x)/(1- cot^2 x)

Tutors, please sign in to answer this question.

1 Answer

 
(sin^6 x)/(1-tan^2 x) + (cos^6 x)/(1-cot^2 x)
= sin^6 x/(1 - sin^2 x/cos^2 x) + cos^6 x/(1 - cos^2 x/sin^2 x)
= sin^6 x cos^2 x/(cos^2 x - sin^2 x) + cos^6 x sin^2 x/(sin^2 x - cos^2 x)
= sin^2 x cos^2 x (sin^4 x - cos^4 x)/(cos^2 x - sin^2 x)
= sin^2 x cos^2 x (sin^2 x - cos^2 x)(sin^2 x + cos^2 x)/(cos^2 x - sin^2 x)
= -sin^2 x cos^2 x <==Answer
-------
Attn:
sin^2 x + cos^2 x = 1